International investment law and the global financial architecture - Tams, Christian J.; Schill, Stephan W., 1976-; Hoffman, Rainer (Frankfurt investment and economic law series, 2017)
The global crises of the early 21st century have tested the international financial architecture. In seeking to ensure stability, governments have regulated financial and capital markets. This in turn has implicated international investment law, which investors have invoked as a shield against debt restructuring, bail-ins or bail-outs. This book explores whether investment law should protect against such regulatory measures, including where these have the support of multilateral institutions. It considers where the line should be drawn between legitimate regulation and undue interference with investor rights and, equally importantly, who draws it. Across the diverse chapters herein, expert international scholars assess the key challenges facing decision makers, analyse arbitral and treaty practice and evaluate ways towards a balanced system of investment protection in the financial sector. In doing so, they offer a detailed analysis of the interaction between investment protection and financial regulation in fields such as sovereign debt restructuring and bank rescue measures. Combining high-level analysis with a detailed assessment of controversial legal issues, this book will provide guidance for both academics and legal practitioners working in international economic law, international arbitration, investment law, international banking and financial law.